Efektivitas Model Pembelajaran Problem Solving dan Problem Posing Ditinjau dari Kemampuan Berpikir Kritis Matematika Siswa Kelas 4 - Wahyu Wulandari; Wahyudi (LPPM Universitas Buana Perjungan Karawang, 2020)
The purpose of this research is to see the effectiveness of the learning model of Problem Solving and Problem Posing in terms of the critical thinking skills of 4th grade students.the subject of this research is 4th grade in Bringin Elementary School 01 as 28 students dan Bringin 02 elementary school as 24 students. Data collection techniques using observation and tests. The research instrument uses RPP Problem Solving and Problem Posing, than istrument of students critical thinking. Data analysis used was quantitative description analysis as a prerequisite test, T test, and N-Gain. The results of hypothesis testing, with the t-sig (2-tailed) test obtained 0,000 < 0,05 with tcount 4,812 > ttable 2,012 then H0 is rejected which means there are differences in the critical thinking mathematics skills. That’s can provable with increase critical thinking students grade 4th in Bringin 01 Elementary School use Problem Solving model with first condition is 70,43 increase 15%. The increase of critical thinking students grade 4 in Bringin 02 Elementary School used Probem Posing with first condition is 70,43 increase be 87,18 with increase 17%. This condition to indicate Problem Posing model more effective than Probem Solving model reviewed by increased critical thinking mathematics.